Beyond Financial Literacy: Lifestyle, Impulse Buying, and Financial Management of Millennial Public Employees - Suriyani, Ni Kadek Heny; Suci, Ni Made; Yudiaatmaja, Fridayana (International Ecsis Association, 2026)
This study examines the effects of financial literacy, lifestyle, and impulse buying behavior on the financial management of Millennial Generation employees in the Government of Buleleng Regency, both partially and simultaneously. The research is driven by the growing complexity of personal financial management among millennials, influenced by changing consumption patterns, easier access to financial products, and evolving lifestyles. A quantitative approach with a survey method was applied. Data were collected through structured questionnaires distributed to employees and analyzed using multiple linear regression to test the relationships among variables. The findings reveal that financial literacy has a positive and significant effect on financial management, indicating that employees with higher financial knowledge are better at planning, managing income and expenses, and making rational financial decisions. Lifestyle also shows a positive and significant influence, where a rational and well-controlled lifestyle supports financial stability and long-term planning. In contrast, impulse buying behavior has a negative and significant effect, as unplanned purchases increase unnecessary spending and reduce financial control. Simultaneously, all three variables significantly affect financial management, explaining 54.8% of its variance. The study highlights the importance of financial education and employee welfare programs to strengthen financial management capabilities.